Color stability of conventional and bulk fill composite resins - Trevisan, Tamara Carolina; Gusson JÚnior, Marcelo; Bortolatto, Janaína Freitas; Pigossi, Suzane; Oliveira JÚnior, Osmir Batista De; Ricci, Weber Adad (Faculdade São Leopoldo Mandic, 2018)
ABSTRACTObjective: This study compared the color stability of different dental composite resins after prolonged exposure to a coffee solution.Methods: Sixty-four cylindrical discs (10 mm diameter x 2 mm thickness) were prepared using 8 different dental composite resins (n=8, per group). The specimens were first immersed in artificial saliva for 24 h followed by immersion in a coffee solution for 14 days. The assessment of chromatic variation (ΔE) was performed with the aid of a Vita Easyshade Advanced spectrophotometer (VITA Zahnfabrik, Bad Sackingen, Germany). The color of each specimen was calculated based on the L*, a* and b* coordinates of the CIELab system.Results: Grandio SO had the lowest average chromatic variation (ΔE=7.77) after immersion in coffee solution. Durafill VS, Grandio and Z350 XT (ΔE=8.58; ΔE=9.52; ΔE=10.39, respectively) showed similar chromatic variation, with no statistical difference in relation to Grandio SO. However, the other dental composite resins evaluated showed statistically higher values of ΔE compared to Grandio SO, and Enamel HRi (ΔE=20.56) demonstrated the highest chromatic variation.Conclusion: The Bulk Fill and hybrid composite resins from the same manufacturer (Micerium, Avegno, Italy) showed greater chromatic variation than the other composite resins tested. Grandio SO (Voco, Cuxaven, Germany) had the lowest ΔE variation.

RESUMOObjetivo: Comparar diferentes resinas compostas em relação á estabilidade de cor após exposição prolongada em solução de café.Métodos: Sessenta e quatro discos cilíndricos (10mm x 2mm) foram confeccionados a partir de 8 diferentes marcas comerciais de compósitos (n= 8 por grupo); os espécimes foram imersos em saliva artificial, e posteriormente em café, sendo por conseguinte feita a avaliação da variação cromática (ΔE), utilizando espectrofotômetro Vita Easyshade Advanced (VITA Zahnfabrik, Bad Sackingen, Germany). O padrão de cada espécime foi medido examinando as coordenadas L*, a* e b* do sistema CIELab.Resultados: A resina composta Grandio SO apresentou a menor média de variação cromática (ΔE= 7,77) após a imersão em solução de café. Semelhantemente, a variação cromática das resinas compostas Durafill VS, Grandio e Z350 XT (ΔE=8,58; ΔE=9,52; ΔE=10.39) que não apresentaram diferença estatística. Todavia, as demais resinas compostas avaliadas apresentaram valores estatisticamente maiores de ΔE em relação a resina Grandio SO, sendo que a resina Enamel HRi (ΔE= 20,56) apresentou a maior variação cromática registrada.Conclusão: As resinas da categoria bulk fill e as resinas híbridas produzidas pelo mesmo fabricante (Micerium, Avegno, Itália) tiveram alterações cromáticas superiores às demais resinas testadas sendo que a resina GrandioSO (Voco, Cuxaven, Alemanha) foi a que apresentou menor alteração de ∆E.
Estabilidade cromática de resinas convencionais e resinas bulk fill
Keywords: Biomimetic; Color; Composite resins.; Biomimética; Cor; Resinas compostas.